2021
DOI: 10.1002/advs.202003636
|View full text |Cite
|
Sign up to set email alerts
|

The CNOT4 Subunit of the CCR4‐NOT Complex is Involved in mRNA Degradation, Efficient DNA Damage Repair, and XY Chromosome Crossover during Male Germ Cell Meiosis

Abstract: The CCR4-NOT complex is a major mRNA deadenylase in eukaryotes, comprising the catalytic subunits CNOT6/6L and CNOT7/8, as well as CNOT4, a regulatory subunit with previously undetermined functions. These subunits have been hypothesized to play synergistic biochemical functions during development. Cnot7 knockout male mice have been reported to be infertile. In this study, viable Cnot6/6l double knockout mice are constructed, and the males are fertile. These results indicate that CNOT7 has CNOT6/6L-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…To our knowledge, RAD51AP2 is the first protein that specifically participates in PAR DSB repair for ensuing XY crossover formation but is dispensable for autosomal crossover formation. Several genes have been reported to increase precocious XY separation during meiosis due to defects in DSB repair after disruption in mice (19,22,(45)(46)(47)(48)(49). It should be noted that all these genes, when mutated in mice, not only increased the frequency of XY separation but also impaired autosomal chromosome behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, RAD51AP2 is the first protein that specifically participates in PAR DSB repair for ensuing XY crossover formation but is dispensable for autosomal crossover formation. Several genes have been reported to increase precocious XY separation during meiosis due to defects in DSB repair after disruption in mice (19,22,(45)(46)(47)(48)(49). It should be noted that all these genes, when mutated in mice, not only increased the frequency of XY separation but also impaired autosomal chromosome behaviors.…”
Section: Discussionmentioning
confidence: 99%
“… 34 It has been reported that from mid-pachytene to diplotene, DSB repair is mainly mediated by nonhomologous end joining (NHEJ) and comprises Ku70 and XRCC4 to repair DSB on the autosomes and 53BP1 to repair DSB on the XY chromosomes. 35 , 36 In meiosis I spermatocytes, the phosphorylated form of histone variant H2AX (γH2AX) marks sites of DNA damage throughout the nucleus, and as DNA is repaired, it remains on the sex chromosomes. 37 Because CHD2 is highly expressed in meiosis I spermatocytes and previous studies have shown that CHD2 is involved in NHEJ repair to promote DSB repair, 28 we wanted to know whether Chd2 haploinsufficiency would cause impaired DNA damage repair during mouse spermatogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are required to clarify the exact function of these genes in cryptorchidism-related infertility, and whether they could become candidate drug targets to prevent and treat cryptorchidism-related infertility. Yes [34,35] The CNOT4 subunit of the CCR4-NOT complex is crucial in male germ cell meiosis mediating multiple important processes such as XY chromosome crossover [34]. CAF1 (part of the CCR4-NOT complex) was essential for spermatogenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…To seek the association of hub genes with cryptorchidism-related infertility, we retrieved the published literature for possible proof. Though no hub gene was found exactly involved in cryptorchidism-related infertility, ten genes (CCR4, LMNB1, LMNB1, MTNR1B, TAC3, TRHR, TRHR, RAD54L, CCNA1, SMC1B, GPRC6A, SYCE2) played a key role in infertility or spermatogenesis [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], indicating that these hub genes might be involved in cryptorchidism-related infertility. Additionally, there was no direct evidence of the function of CHRM4 and TAS2R19 in infertility.…”
Section: Function Of Hub Genes In Cryptorchidism-related Infertilitymentioning
confidence: 99%